A Single-Channel Speech Enhancement Algorithm Combined with Time-Frequency Mask. Issue 1 (1st December 2022) - Yu, Bowen; Zeng, Qingning
Abstract : Aiming at the problem of noise overestimation when the classical single-channel speech enhancement method suppresses noise, single-channel speech enhancement method on the basis of the time-frequency mask is put forward to improve the quality of speech enhancement and separation. First, we estimate the noise and prior signal-to-noise ratio from the noisy speech, calculate the time-frequency mask and finally combine noisy speech synthesis to enhance the speech. Adaptive time-frequency mask combines IBM and IRM to avoid over-suppressing noise. In this paper, noisy speech is processed by an improved time-frequency mask combined with SNR. The algorithm combines the advantages of the single-channel algorithm and time-frequency mask. The experimental results indicate that this method significantly improves the signal-to-noise ratio, is robust, and is easy to use.